2022
DOI: 10.3389/fpsyt.2022.816893
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Dexmedetomidine for the Treatment of Pre-operative Anxiety and Insomnia: A Prospective, Randomized, Controlled, and Clinical Trial

Abstract: Background and ObjectiveSeveral patients with pre-operative anxiety and insomnia refuse to take sleeping pills because of the side effects of sleeping pills. This study aimed to evaluate the applicability of intranasal dexmedetomidine (DEX) in the treatment of pre-operative anxiety and insomnia.MethodsA total of 72 patients with insomnia and anxiety were randomly divided into two groups of intranasal DEX (n = 36) and intranasal normal saline (NS, n = 36). The primary outcomes included patients' time to fall as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…For example, in humans, sub-anesthesia levels of ketamine, an NMDA receptor antagonist, produces robust, quick-onset, and long-lasting anxiolysis on patients with refractory anxiety disorders or social anxiety disorders [8][9][10] . Dexmedetomidine, an a2adrenergic receptor agonist, alleviated anxiety-like behaviors in a rodent model of posttraumatic stress disorder (PTSD) 11 and in nerve ligation-induced chronic pain 12 , and has long been used to provide peri-operative anxiolysis in animals and human patients [13][14][15] . Sevoflurane, a GABA-receptor potentiator, also reversed the long-term anxiety-like behaviors caused by a single episode of formalin induced inflammatory pain in rodents 16 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, in humans, sub-anesthesia levels of ketamine, an NMDA receptor antagonist, produces robust, quick-onset, and long-lasting anxiolysis on patients with refractory anxiety disorders or social anxiety disorders [8][9][10] . Dexmedetomidine, an a2adrenergic receptor agonist, alleviated anxiety-like behaviors in a rodent model of posttraumatic stress disorder (PTSD) 11 and in nerve ligation-induced chronic pain 12 , and has long been used to provide peri-operative anxiolysis in animals and human patients [13][14][15] . Sevoflurane, a GABA-receptor potentiator, also reversed the long-term anxiety-like behaviors caused by a single episode of formalin induced inflammatory pain in rodents 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Dex has been shown to have neuroprotective effects both in vivo and in vitro [13][14][15] and these effects are increasingly considered to have clinical implications. Because Dex sedation is closer to the characteristics of natural sleep [16], Dex is often used to improve the sleep quality of perioperative patients and critically ill patients [17][18][19][20][21]. Previous studies have shown that dexmedetomidine can improve the emotional behavior [22] and cognitive dysfunction [23] caused by sleep deprivation but the mechanism is not clear.…”
Section: Introductionmentioning
confidence: 99%